Meta - Perspective Performance Measurement Scale Review and Validity Check for Employees of an Indian Organization - Barman, Arup; Seshadri, S. B. (Prabandhan: Indian Journal of Management, 2009)
Measurement of meta-perspective performance of employees in an organizational setting is the latest addition to the research tools for measuring the performance of employees. The freshness of this tool and approach to measurement of employees’ performance has motivated the researchers to examine applicability of the contents in an organizational setting of Life Insurance Corporation. Present paper aims to validate the contents of original scale in the context of Life Insurance Corporation of India. The author added a few items to original scale and tested validity for different groups of respondents.